PELAKSANAAN TUGAS GURU DALAM MENINGKATKAN PRESTASI BELAJAR SISWA MELALUI BELAJAR KELOMPOK - Khoirul anwar (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2020)
Abstract: The main problem in this research is how a teacher can improve student achievement. There are many ways to improve student achievement, including group study. Group learning here is learning carried out by more than one person in group learning. By learning groups of students can work together and exchange ideas between one student and another. so that students who are weak will be helped by students who have more advantages in learning. Student learning achievement is the result achieved by students after carrying out teaching and learning activities. In teaching and learning activities, there are many methods used to improve student achievement. In this research, the method used is the group learning method